Relationships between a load-velocity profile and sprint performance in butterfly swimming - Gonjo, T.; Eriksrud, O.; Papoutsis, F.; Olstad, B. H. (International Journal of Sports Medicine, 2020)
The purpose of this study was to establish the relationships between 50 m sprint swimming performance and variables acquired from a swimming load-velocity profile established by semi-tethered butterfly swimming. Twelve male elite swimmers participated in the present study and performed 50 m sprint and semi-tethered butterfly swimming with different loads. The mean velocity among all upper-limb cycles was obtained from the 50 m swimming (race velocity), and maximum load and velocity were predicted from the load-velocity profile established by the semi-tethered swimming test. There was a very large correlation (r=0.885, p<0.01) and a high intra-class correlation (0.844, p<0.001) between the race velocity and the predicted maximum velocity. Significant correlations were also observed between the predicted maximum load and the 50 m time as well as the race velocity (r=- 0.624 and 0.556, respectively, both p<0.05), which imply that an ability to achieve a large tethered swimming force is associated with 50 m butterfly performance. These results indicate that the load-velocity profile is a useful tool for predicting and assessing sprint butterfly swimming performance.